2016
DOI: 10.1016/j.kint.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Iron management in chronic kidney disease: conclusions from a “Kidney Disease: Improving Global Outcomes” (KDIGO) Controversies Conference

Abstract: Before the introduction of erythropoiesis-stimulating agents (ESAs) in 1989, repeated transfusions given to patients with end-stage renal disease caused iron overload, and the need for supplemental iron was rare. However, with the widespread introduction of ESAs, it was recognized that supplemental iron was necessary to optimize hemoglobin response and allow reduction of the ESA dose for economic reasons and recent concerns about ESA safety. Iron supplementation was also found to be more efficacious via intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
236
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 302 publications
(254 citation statements)
references
References 127 publications
(127 reference statements)
4
236
0
8
Order By: Relevance
“…Despite a relatively high prevalence of anemia, relatively few patients with stages 4-5 CKD are treated with intravenous (IV) iron, 10 owing to associated risks including anaphylactoid reactions, concerns regarding the need for multiple venous cannulations in patients who may require creation of arteriovenous fistula for hemodialysis, and a variety of logistic hurdles. 11,12 Ferric citrate functions as an intestinal phosphate binder, and has been approved by the US Food and Drug Administration and other major regulatory agencies for the treatment of hyperphosphatemia in patients on dialysis. 13,14 Prior studies in patients receiving dialysis and a phase 2 study in patients with NDD-CKD found ferric citrate to increase transferrin saturation, serum ferritin, and hemoglobin.…”
mentioning
confidence: 99%
“…Despite a relatively high prevalence of anemia, relatively few patients with stages 4-5 CKD are treated with intravenous (IV) iron, 10 owing to associated risks including anaphylactoid reactions, concerns regarding the need for multiple venous cannulations in patients who may require creation of arteriovenous fistula for hemodialysis, and a variety of logistic hurdles. 11,12 Ferric citrate functions as an intestinal phosphate binder, and has been approved by the US Food and Drug Administration and other major regulatory agencies for the treatment of hyperphosphatemia in patients on dialysis. 13,14 Prior studies in patients receiving dialysis and a phase 2 study in patients with NDD-CKD found ferric citrate to increase transferrin saturation, serum ferritin, and hemoglobin.…”
mentioning
confidence: 99%
“…Recent clinical practice guidelines from Kidney Disease: Improving Global Outcomes recommend using oral or intravenous iron before erythropoietin‐stimulating agents for the treatment of iron deficiency anemia in patients with nondialysis‐dependent (NDD)‐CKD 1. Oral iron preparations are typically ineffective and/or poorly tolerated due to gastrointestinal side effects 1.…”
mentioning
confidence: 99%
“…Oral iron preparations are typically ineffective and/or poorly tolerated due to gastrointestinal side effects 1. Intravenous iron is used infrequently in nephrology offices as it requires intravenous infusion in a monitored setting with facilities for resuscitation because of risks of serious adverse drug events, including hypersensitivity reactions 1…”
mentioning
confidence: 99%
“…These findings have led to several editorials and position articles highlighting the potential dangers of excessive use of IV iron products [9,15,16] as well as the inadequacy of the guidelines proposed by KDIGO-2012 (Kidney Disease Improving Global Outcomes) and the iron biomarker targets set by KDOQI-2006 (Kidney Disease Outcomes Quality Initiative) and the older ERA-EDTA-2009 position paper (European Renal Association-European Dialysis and Transplant Association), by opposition to the newer ERA-EDTA-2013 position paper, with a view to protect end-stage renal disease (ESRD) patients from iron overload [4,17,18]. They also contributed to the organization of the KDIGO Controversies Conference on iron management in chronic kidney disease, which took place in San Francisco on March 27-30, 2014 [19]. This conference was attended by nephrologists, hematologists, hepatologists and specialists in iron metabolism.…”
Section: G Rostoker (France)mentioning
confidence: 99%
“…This conference was attended by nephrologists, hematologists, hepatologists and specialists in iron metabolism. Its consensus statements recognized the "iron overload'' entity in hemodialysis patients and called for a specific research agenda [19]. Finally, in June 2015 the Dialysis Advisory Group of the American Society of Nephrology published an updated recommendation on uncertainties of usage of high-dose of intravenous iron in hemodialysis patients [20].…”
Section: G Rostoker (France)mentioning
confidence: 99%